The Effect of a Statewide Policy on High School Emergency Action Plans - Samuel T. Johnson; Michael C. Koester; Viktor E. Bovbjerg; Marc F. Norcross (Sports, 2022)
Institutions sponsoring athletics must be prepared for emergencies. Due to this, more governing bodies are requiring a sports-related emergency action plan (EAP). Yet, the effects of these policies are unknown. We compared adoption of EAPs and associated best practices in Oregon high schools before and after a policy requiring an EAP. Athletic directors were invited to complete a survey during the year before the policy went into effect and again the following year. We assessed whether the school had a written EAP and if they did, was the EAP venue specific, available at the venue, distributed to personnel, and annually reviewed and rehearsed. Pre/post-policy proportions were analyzed using Fisher exact tests for all schools and then schools that completed both surveys. There was a significant increase of schools that reported having an EAP after the policy went into effect (all schools: 55% to 99% [p < 0.001] and schools responding both years: 60% to 98% [p < 0.001]). Venue specific EAPs also significantly increased but only when analyzing all responses (59% to 71% [p = 0.03]). No best practice recommendations related to EAP availability, distribution, review, or rehearsal changed after the policy. Schools met the minimum requirements of the policy, but other related best practices did not significantly improve.